66 GRIP STRENGTH, ONLY A PHYSICAL TASK? ASSOCIATIONS BETWEEN RESTING-STATE BRAIN CONNECTIVITY AND GRIP STRENGTH. (25th October 2022) - Davis, JRC; Boyle, R; Knight, SP; Romero-Ortuño, R; Zúñiga, RG
Abstract: Background: Grip strength (GS) is a simple measure used in the assessment of frailty and sarcopenia. Despite being physical, studies show that it is also related with depression and cognition. Our aim was to explore if brain connectivity is implicated in GS. Methods: Participants from Wave 3 of TILDA with adequate resting-state functional-MRI data were included. Connectome-based predictive modelling was used on Shen parcellated brain connectivity matrices to find connections that are positively and negatively associated with grip strength: positive and negative networks (PN and NN). On each iteration of a randomized 10-fold cross-validation, the training folds were utilized to perform partial Spearman correlations (age-, sex-adjusted) between each connection and GS. Significant (p<0.001) connections were selected. PN and NN strengths were computed by summing across all significant correlations. Linear models regressing GS on network strengths were built on training data and used to predict GS in the test fold. After 10 folds were complete the performance was measured via Pearson R between predicted and true GS values. This 10-fold process was repeated 1000 times and a mean R obtained. Permutation significance testing was employed where the cross-validation procedure was repeated 1000 times, with GS randomly shuffled each time. The P-value was the proportion of permuted R values >= the mean R. Results: 317 participants were included (mean(SD) age 67.3(7.2) and 49.8% female). For PN: R[95% intervals]=0.29[0.26, 0.32], P<0.001 and for NN: R=0.24[0.20, 0.28], P<0.001. In both, the default mode, dorsal attention, and cerebellum networks were highly involved but with differing patterns: most notable was the presence of high connectivity between both cerebellar hemispheres in the PN but not in the NN. Conclusion: Grip strength is related with different brain connectivity patterns suggesting the involvement of networks beyond motor areas. Further studies are required to disentangle the neuroscience behind this clinically relevant physio-cognitive task.